The α-Gal Syndrome and Potential Mechanisms - Román-Carrasco, Patricia; Hemmer, Wolfgang; Cabezas-Cruz, Alejandro; Hodžić, Adnan; de la Fuente, José; Swoboda, Ines (Frontiers in Allergy, 2021)
The α-Gal syndrome is a complex allergic disease characterized by the development of specific IgE antibodies against the carbohydrate galactose-α-1,3-galactose (α-Gal), an oligosaccharide present in cells and tissues of non-primate mammals. Individuals with IgE antibodies to α-Gal suffer from a delayed form of anaphylaxis following red meat consumption. There are several features that make the α-Gal syndrome such a unique allergic disease and distinguish it from other food allergies: 1) symptoms causing IgE antibodies are directed against a carbohydrate moiety, 2) the unusual delay between the consumption of the food and the onset of the symptoms, 3) the fact that primary sensitization to α-Gal occurs via tick bites. This review takes a closer look at the immune response against α-Gal, in healthy and in α-Gal allergic individuals. Furthermore, the similarities and differences between immune response against α-Gal and against the other important glycan moieties associated with allergies, namely cross-reactive carbohydrate determinants (CCDs), are discussed. Then different mechanisms are discussed that could contribute to the delayed onset of symptoms after consumption of mammalian meat. Moreover, our current knowledge on the role of tick bites in the sensitization process is summarized. The tick saliva has been shown to contain proteins carrying α-Gal, but also bioactive molecules, such as prostaglandin E2, which is capable of stimulating an increased expression of anti-inflammatory cytokines while promoting a decrease in the production of proinflammatory mediators. Together these components might promote Th2-related immunity and trigger a class switch to IgE antibodies directed against the oligosaccharide α-Gal. The review also points to open research questions that remain to be answered and proposes future research directions, which will help to get a better understanding and lead to a better management of the disease.